Assessment of adaptability parameters in hulled oat germplasm accessions in terms of their yield in the environments of Kirov Province - M. V. Tulyakova; G. A. Batalova; I. G. Loskutov; S. V. Permyakova; N. V. Krotova (Труды по прикладной ботанике, генетике и селекции)
Background. Studying the gene pool of a crop under specific soil and climate conditions makes it possible to predict the breeding value of germplasm, while its subsequent inclusion in the breeding process ensures the development of adaptable cultivars capable of implementing their productive potential in large-scale agriculture.Materials and methods. Stability (Si2) and plasticity (bi; PUSS), Ambient Condition Index (Ij), Homeostatic (Hom), Stress Resistance, and Stability Index (Is) were calculated for 12 hulled oat (Avena sativa L.) accessions at the FARC of North-East.Results. Accessions 2981 IG100720 (USA) and k-15293 BORYNA (Poland) showed the best stress resistance, while the highest genetic flexibility was observed in 2981 IG100720 (USA), 3007 IG100848 (Germany), 5330 СSI  590/05,  and k-15178 ‘Begunok’ (Russia). Sources of intensive-type hulled oats: k-15330 CSI 590/05 (Russia) (bi = 1.36)  and  k-15331 CSI 2167/03 (Russia) (bi = 1.60),  were  identified for their higher yield values: 856 and 889 g/m2 under improved growing conditions in 2017, and 365 and 285 g/m2 under dry conditions in 2016, respectively. Medium-intensive accessions k-15178 ‘Begunok’ (Russia) (bi = 1.07), and ‘Skrokolik’ (k-15321, Russia) (bi = 0.97) were identified for the best plasticity. The reference cv. ‘Krechet’ (Si2 = 0.06) demonstrated high yield stability.Conclusion. Sources were selected for hulled oat breeding: 2981 IG100720 (USA), 3007 IG100848 (Germany), and k-15293 BORYNA (Poland), with high stress resistance and plasticity, and plastic sources k-15178 ‘Begunok’ and k-15321 ‘Skrokolik’ (Russia), with stable high yield under varying environmental conditions.